Characterizing the importance of habitat patches in maintaining landscape connectivity for Tibetan antelope in the Altun Mountain National Nature Reserve, China. Issue 6 (26th August 2014) - Zhao, Haidi; Liu, Shiliang; Dong, Shikui; Su, Xukun; Liu, Qi; Deng, Li
Abstract: Connectivity of habitat patches is crucial for wildlife dispersal and survival, and identifying patches with high importance for maintaining connectivity can aid effective wildlife management. Knowledge of the habitat distribution of the Tibetan antelope in the Altun Mountain National Nature Reserve, which is essential for connectivity analysis, remains limited. We analyzed potential habitat distribution and priority patches using GIS‐based habitat suitability modeling with three weighting factors and evaluated the connectivity of habitat patches under four dispersal distance scenarios. Patches with high habitat suitability covered 25.39 % of the total area, and these patches were selected for connectivity analysis as resource patches. Connectivity analysis indicated that, although the overall probability of connectivity (PC) showed an upward trend with increasing dispersal distance, the importance of each patch varied considerably under different dispersal distance scenarios. Transfer analysis of patch numbers between different importance levels revealed that the number of patches becoming less important was higher than the number of patches becoming more important when dispersal distance increased. In addition, nine patches covering 38.49 % of the suitable habitat area were identified as priority patches, in particular the patches near the Kardun and the Karchuka inspection stations. We also found that the habitat distribution of the Tibetan antelope obtained from the suitability model matched the population distribution determined by a field survey. Correlation analysis between patch area and the percentage of PC index value loss (dPC) revealed that the larger patches in this region were more likely to be important for maintaining connectivity.